Therapeutic drug monitoring‐guided definition of adherence profiles in resistant hypertension and identification of predictors of poor adherence. (15th August 2018) - Avataneo, Valeria; De Nicolò, Amedeo; Rabbia, Franco; Perlo, Elisa; Burrello, Jacopo; Berra, Elena; Pappaccogli, Marco; Cusato, Jessica; D'Avolio, Antonio; Di Perri, Giovanni; Veglio, Franco
Abstract : Aims: Arterial hypertension is an important cardiovascular risk factor. A substantial proportion of patients show resistance to antihypertensive treatment but poor adherence to medication regimens is also a significant cause of treatment failure. In this context, therapeutic drug monitoring (TDM) could be useful. The objective of this study was to assess adherence to treatment in patients with resistant hypertension by TDM and to identify parameters that predict nonadherence. Methods: Liquid chromatography tandem mass spectrometry was used to quantify a wide panel of antihypertensive drugs in human plasma to assess treatment compliance. Associations between TDM‐determined adherence profiles, self‐reported adherence and other patient‐related clinical, anthropometric or demographic features were evaluated as potentially useful pre‐TDM predictors of poor adherence. Results: TDM was performed on 50 patients with suspected resistant hypertension: 24% of patients partially complied to treatment and 18% were nonadherent. No concordance was observed with questionnaire results, while nonadherence was associated with high diastolic blood pressure, high heart rate, previous onset of stroke and previous use of invasive treatments, including renal denervation or baroreceptor stimulation. Conclusions: This evidence highlights the high prevalence of poor adherence in patients with resistant hypertension and the need for caution in using invasive approaches. These preliminary data require validation in a larger cohort, to confirm the need for TDM in routine clinical practice.